Implementasi Media Flashcard Untuk Meningkatkan Keterampilan Calistung Peserta Didik - Zuhriawan, M. Qoyum; Khotimah, Khusnul; Prameswari, Lintang (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
The Covid-19 pandemic from 2020 to 2022, which lasted for approximately three years, caused online learning, so that learning was less than optimal, which caused female students to be less proficient in reading, writing and calculating. Reading, writing and calculating are very important because they are the main foundation for continuing to a higher grade level. Therefore, in this community service, we will provide media that can help students learn calistung more quickly, namely Flashcard media. This is also the main objective of implementing this community service, namely helping students to learn happily, so that students can easily understand and be faster in reading, writing and basic calculations. The subjects in this service are students of the Miftahul Huda Madrasah Ibtidaiyah class 1 to class 3. Based on the results of the Flashcard media application, there are differences in students' understanding after using it. Keywords: learning media, flashcards, calistung skills